Numerical Segregation of the Effects of Body Forces in a Rotating, Differentially Heated Enclosure - Tso, C. P.; Jin, L. F.; Tou, S. K. W. (TAYLOR & FRANCIS INC, 2007)
The effects of Coriolis force, centrifugal force, and thermal buoyancy force are segregated numerically on an air-filled, differentially heated enclosure of square cross section, with the enclosure rotated about its horizontal axis. The physically realizable periodic oscillation solutions are identified with reported experimental results of six temperature fields. The evolution of the flow pattern in the natural-convection flow fields are studied from stationary to increasing rotation of the enclosure. The effects of Coriolis force and centrifugal force on the natural convection are small and are differentiated from those of other forces.